A network approach to mixing delegates at meetings - Federico Vaggi; Tommaso Schiavinotto; Jonathan LD Lawson; Anatole Chessel; James Dodgson; Marco Geymonat; Masamitsu Sato; Rafael Edgardo Carazo Salas; Attila Csikász-Nagy (eLife, 2014)
Delegates at scientific meetings can come from diverse backgrounds and use very different methods in their research. Promoting interactions between these ‘distant’ delegates is challenging but such interactions could lead to novel interdisciplinary collaborations and unexpected breakthroughs. We have developed a network-based ‘speed dating’ approach that allows us to initiate such distant interactions by pairing every delegate with another delegate who might be of interest to them, but whom they might never have encountered otherwise. Here we describe our approach and its algorithmic implementation.